The community networking handbook - Bajjaly, Stephen T. (ALA editions., 1999)
The Community Networking Handbook surveys the complete process of community networking: planning, developing partnerships, funding, marketing, content, public access, and evaluation. Under the guidance of author Stephen Bajjaly, founder and project director of South Carolina's MidNet, you will learn how the community network works, and how you can play your part.